CHALK THE HEART VOLUME 2 - Nurzarina Abdul Samad; Siti Zaimaliza Masturi; Sarala Thulasi Palpanadan (Penerbit UTHM, 2026)
CHALK THE HEART is a compilation of poems, anecdotes and short stories that entail the essence of education. This compilation delves into the intellectual growth and also emotional roller coaster that occurs both within and outside classroom. The collection captures the joy and obstacles in learning. It also resembles diverse perspectives on transformative educational experiences. Interspersed anecdotes provide glimpses into real-life moments of inspiration and enlightenment. This anthology invites audience to reflect on their own educational journeys and appreciate the teachers and experiences that have shaped their lives.